Margem e rio: precisão e espontaneidade como procedimento de criação do atuante - Sales, Luiz Felipe da Silva (2018)
The present research aims to investigate the concepts of precision and spontaneity as a creative procedure based on creative and pedagogical experiments. Initially revisiting the research paths of Stanislavski and Grotowski, this work is based on the concepts of exhaustion, organicity, contact, physical action and embodiment. The materiality of the body-affection, its relation to the environment, and the questions surrounding the performing an action, became the stimulus of the experiment in my own body through the action of digging, which unfolded in the Poetic Project Pasado que no pasa, presented as homonymous video-performance and as video installation, titled Saudade - a body in a state of exhaustion. Pedagogical unfolding also compose this research where the concepts of precision and spontaneity are evaluated from the perspective of the body of the other, participants of actor and performance workshops held in cities such as Rio Branco (AC) and Macapá (AP) to create performance actions. Margin and River is a dissertation on precision and spontaneity as a procedure of creation for the ocean of the performer acting in the arts of the scene.